The Court of Queen's Bench of Manitoba, 1870-1950 : a biographical history - Brawn, Dale, 1948-; Osgoode Society for Canadian Legal History (Toronto, Ontario : Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2006)
This fascinating study offers an intimate look at personalities ranging from prime ministers to members of the bench and both senior levels of government.
Introduction -- The Red River Settlement becomes a province, 1872 -- A time of controversy, 1872-1878 -- The end of an era, 1879-1884 -- The Manitoba Bar comes of age, 1885-1907 -- The emergence of a provincial elite, 1908-1920 -- A time of transition, 1921-1938 -- A most political bench, 1939-1950 -- Conclusion.
Online resource; title from PDF title page (EBSCO, viewed April 11, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Manitoba. -- Court of Queen's Bench -- Biography; Manitoba. -- Court of Queen's Bench -- History; Manitoba. -- Cour du banc de la reine -- Biographies; Manitoba. -- Cour du banc de la reine -- Histoire; Manitoba. -- Court of Queen's Bench; Judges -- Manitoba -- Biography; Courts -- Manitoba -- History; Juges -- Manitoba -- Biographies; Tribunaux -- Manitoba -- Histoire; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; Courts; Judges; Manitoba; Biographies; History; Biographies; Biographies